Root Regeneration in Auxin Supplemented Media in In vitro and Acclimatisation of Dendrobium cv. Sonia Earsakul - K. S. Sebastian; Laisharam Hemanta; Khamrang Mathukmi (Research Highlights in Agricultural Sciences Vol. 1, 2022)
The Study was conducted during 2017-2019 at the Tissue Culture Laboratory, Department of Horticulture, NU: SASRD, Nagaland to study the influence of different auxins in varied doses on in vitro root regeneration of Dendrobium cv. Sonia Earsakul and percentage of survival during hardening. The experiment was laid out in Completely Randomized Design with thirteen different treatments with three replications and ten plant samples. The data collected were tested by Analysis of Variance (ANOVA) and the difference among the treatment mean were tested by Duncan’s Multiple Range Test. The different treatments used are IBA, NAA and IAA in concentration level of 0, 0.5, 1, 1.5 and 2 mg L-1 respectively. According to the study, IBA at 1 mg/l produced the longest roots (5.97 cm) and shoots (7.8 cm) among the various treatments, as well as the highest survival rates during primary hardening (34.30%) and secondary hardening (94.29%).